The Diabetes Unmet Need with Basal Insulin Evaluation (DUNE) study in type 2 diabetes: Achieving HbA1c targets with basal insulin in a real‐world setting. Issue 6 (28th March 2019) - Meneghini, Luigi F.; Mauricio, Didac; Orsi, Emanuela; Lalic, Nebojsa M.; Cali, Anna M.G.; Westerbacka, Jukka; Stella, Peter; Candelas, DEA, Christophe; Pilorget, Valerie; Perfetti, Riccardo; Khunti, Kamlesh; ,
Abstract : Aims: To describe in a real‐world setting the achievement of physician‐selected individualized HbA1c targets in individuals with type 2 diabetes, newly or recently initiated with basal insulin, and the association of hypoglycaemia with target achievement. Materials and methods: A 12‐week, prospective, single‐arm, observational study of adults with type 2 diabetes, either newly initiated with any basal insulin or start on basal insulin within the preceding 12 months. At enrollment, eligible participants from 28 countries were treated with or without oral antihyperglycaemic drugs and/or GLP‐1 receptor agonists. Results: Individualized targets for almost all of the 3139 evaluable participants (99.7%) had been set by their physicians, with 57% of participants having HbA1c targets between 7.0% and <7.5% (53 and <58 mmol/mol). By week 12, 28% and 27% of newly and previously initiated participants, respectively, achieved individualized HbA1c targets with modest average increases in daily insulin dose of 9 and 5 U (0.10 and 0.06 U/kg), respectively, from baseline (14 and 23 U [0.17 and 0.29 U/kg], respectively). Overall, 16% of participants experienced at least one episode of hypoglycaemia. Both the incidence and frequency of hypoglycaemia, but not the severity, were positively associated with a higher likelihood of achieving individualized HbA1c targets ( P  < 0.05). Conclusions: In this prospective real‐world study, most participants using basal insulin did not achieve the individualized HbA1c targets set by their physicians. Participants who experienced symptomatic hypoglycaemia were more likely to achieve HbA1c targets than those who did not.